Efeito da radioterapia e do flúor na perda mineral, nas propriedades mecânicas e na morfologia do esmalte submetido a ciclagem de pH in vitro - Lopes, Camila de Carvalho Almança (2016)
The aim of this of this study was to evaluate the effect of radiotherapy, associated or not with fluoride topical application, on chemical composition, mechanical properties and morphology of enamel demineralization in vitro. Thirty third molars were randomly divided into three groups (n=10): Non-irradiated enamel (NI); Irradiated enamel in relative humidity (IH), Irradiated enamel in neutral sodium fluoride gel (IF). Each group was also subdivided into two subgroups accordingly to the presence of pH cycling: with or without pH cycling. The teeth of the IH and IF groups were submitted to a radiation protocol of 2 Gy daily, five days per week, per seven weeks, totalizing 70 Gy. Chemical composition changes were measured by Fourier Transform Infrared Spectrometry (FTIR). The analyzed parameters were: matrix:mineral ratio (M:M), relative carbon content (RCC) and crystallinity. It was also evaluated the Vickers Microhardness (VHN) and Elastic Modulus (E) at three depths (superficial, middle and deep), Enamel morphology was assessed by scanning electron microscopy (SEM) (n=3). M:M, CRC and crystallinity were analyzed using 2-Way ANOVA and VHN and E data using 3-Way ANOVA, followed by Tukey HSD test (p<0.05). IF without pH cycling had the lowest values of M:M ratio. IH presented the higher E values, followed by IF and NI. The pH cycling promoted reduction in RCC; and increased crystallinity of NI and IF and also increased VHN and E for NI and IF. With the pH cycling, NI showed the lowest E values. SEM images showed no morphological alterations for all groups without pH cycling. With pH cycling, NI showed the greatest discontinuity of the enamel outer morphology. It was concluded that radiotherapy alters the elastic modulus of the enamel. The crystallinity and the phosphate content of the enamel increase after pH cycling, and also increase its mechanical properties. However, diminish the relative carbonate content. The fluoride reduce the organic matrix and maintain the outer morphology of the irradiated enamel